Complexity of adoption and diffusion of ecological sanitation technology: a review of literature. (19th October 2022) - Banamwana, Celestin; Musoke, David; Ntakirutimana, Theoneste; Buregyeya, Esther; Ssempebwa, John; Maina, Gakenia W.; Tumwesigye, Nazarius M.
Abstract: Ecological sanitation (Ecosan) technology was introduced to improve sanitation through the reuse of excreta resources, particularly in developing countries. However, the adoption of Ecosan technology is low which makes its diffusion complex, especially in diverse spatial and socio-cultural contexts. This review of literature aimed to use the innovation theory to identify the issues that make the process of adoption of Ecosan technology complex. A total of 105 published studies were reviewed. Of these, only 34 studies were analyzed and grouped according to the complexity of the diffusion of ecological sanitation technology using the five stages of innovation diffusion conceptual model identified by Everett Rogers namely: knowledge, persuasion, decision, implementation, and confirmation. The studies revealed the existence of diverse complexities of adoption, such as lack of sanitation policy, phobia against the use of Ecosan by-products, lack of technical support, and safety issues. In addition, poor practical knowledge, illiteracy, high capital cost, disgust with human excreta, religious taboos, and cultural boundaries were also found to hinder the smooth diffusion of Ecosan technology in various geographical settings. The scale-up of Ecosan technology, therefore, needs to focus on addressing these barriers and adopting implementation best practices. HIGHLIGHTS: This paper highlights stages of adoption of Ecosan in diverse social settings. This paper contextualizes the socio-cultural, financial constraints, and sanitation policies gaps in the transfer of Ecosan. This paper applies the technology diffusion theory to evaluate the current situation of adoption of Ecosan. This paper sets strategies to scale up Ecosan coverage beyond the organization and country level.